Influence of "soft start" polymerization on marginal sealing in resin composite restorations - Blažić Larisa; Živković Slavoljub (Serbian Medical Society - Dental Section, Belgrade, 2003)
The purpose of this study was to evaluate the marginal microleakage in Class II with different materials in resin composite restorations cured by using "soft start" and standard polymerization techniques. Two adhesive Class II cavities were prepared in 50 human teeth with enamel in-between. Samples were divided into 5 groups and filled with composite resins, compatible flow resin composites and bonding systems. The ocluso-mesial restorations were cured with standard curing technique, and the ocluso-distal restorations were cured with "soft start" curing technique. After thermocycling, the teeth were immersed in silver nitrate solution and sectioned for leakage evaluation. The results pointed out, after "soft start" and standard curing techniques, that the best marginal behavior in Class II restorations was obtained with Tetric Ceram / Tetric Flow composite resins, then with Filtek Z 250 / Filtek Flow, followed by Admira Admira Flow and Point / Revolution composite materials. The deepest dye penetration was found in cavities with Diamond Lite / Diamond Link composite restorations. No statistically significant difference was found in the tested composite resin restorations, whether treated with "soft start" polymerization or with standard polymerization technique, in regard to marginal micro leakage.